Project Commercial 108: Salt Research with feeder lambs - Bell, T.D.; Hix, E.L.; Erhart, A.B.; Parrish, D.B.; Underbjerg, G.K.L. (Kansas Agricultural Experiment Station, 2012)
Experiments designed to test the need and value of salt in the rations of feeder lambs have been conducted by the Kansas Agricultural Experiment Station for the past three years. The tests have shown that feedlot gains and feedlot efficiency are reduced when supplemental salt is withheld from the rations of fattening lambs in the feedlot. When the lamb were all slaughtered after a uniform feeding period, the lambs receiving no salt had lower yielding and lower grading carcasses than the lambs given salt.
Keywords: Sheep; Salt; Feed efficiency; Gain